High-Frequency Dynamics of Active Region Moss as Observed by IRIS - Narang, Nancy; Pant, Vaibhav; Banerjee, Dipankar; Van Doorsselaere, Tom (Frontiers in Astronomy and Space Sciences, 2019)
The high temporal, spatial and spectral resolution of Interface Region Imaging Spectrograph (IRIS) has provided new insights into the understanding of different small-scale processes occurring at the chromospheric and transition region (TR) heights. We study the dynamics of high-frequency oscillations of an active region (AR 2376) moss as recorded by simultaneous imaging and spectral data of IRIS. Wavelet transformation, power maps generated from slit-jaw images in Si\,IV\,1400\,Å~passband, and sit-and-stare spectroscopic observations of Si\,IV\,1403\,Å~spectral line reveal the presence of high-frequency oscillations with $\sim$1--2\,minutes periods in the bright moss regions. The presence of such low periodicities is further confirmed by intrinsic mode functions (IMFs) as obtained by empirical mode decomposition (EMD) technique. We find the evidence of the presence of slow waves and reconnection-like events, and together they cause the high-frequency oscillations in the bright moss regions.